When “Home” Becomes the “Field”: Ethical Considerations in Digital and Remote Fieldwork - Konken, Lauren C.; Howlett, Marnie (Perspectives on politics, 2023)
The COVID-19 pandemic has underscored the unpredictability and instability of fieldwork as a method for data collection. As the pandemic prompted unprecedented political dynamism and social and economic disruptions at both domestic and global levels, in-person fieldwork became challenging, if even possible, in the two years following March 2020. While scholars are again using traditional fieldwork methods, we have seen an increased use of digital tools to conduct research remotely since the pandemic due to international travel bans and social distancing measures. Although not yet widely discussed, these new approaches pose new ethical questions as understandings of both our “fields” and “homes” evolve. In this paper, we stress the need for scholars to reconsider how we conceive of our ethical obligations in situations wherein we have conducted research without ever physically accessing our field sites or interacting in person with our participants. We particularly urge researchers to re-evaluate their ethical responsibilities around transparency and replicability in the dissemination and publication of findings when engaging in fieldwork “from home.” These considerations were necessary prior to 2020 but are especially relevant within the context of the pandemic as scholars enter new field sites remotely or return to those previously visited in person. As a result, this paper starts a critical conversation about ethical practices in remote and digital fieldwork, which will continue to prove significant as digital and remote methods are used for data collection in a post-pandemic world.